2021
DOI: 10.1093/ehjdh/ztab083
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation and evaluation of a novel six-lead handheld electrocardiogram recorder compared to the 12-lead electrocardiogram in unselected cardiology patients (EVALECG Cardio)

Abstract: Introduction Handheld ECG monitors are increasingly used by both healthcare workers and patients to diagnose cardiac arrhythmias. There is a lack of studies validating the use of handheld devices against the standard 12 lead ECG. The Kardia 6 L is a novel handheld ECG monitor which can produce a 6 lead ECG. In this study we compare the 6 L ECG against the 12 lead ECG. Methods A prospective study consisting of unselected cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…It was more challenging for the algorithm to obtain interval measurements in abnormal ECGs, therefore impeding clinical application in patients at risk. In another study ( 6 ) using a multilead handheld device, it was shown, that QTc could be obtained by the device most frequent in lead II. Changing of the Scanwatch’s position for recording might lead to more usable data.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It was more challenging for the algorithm to obtain interval measurements in abnormal ECGs, therefore impeding clinical application in patients at risk. In another study ( 6 ) using a multilead handheld device, it was shown, that QTc could be obtained by the device most frequent in lead II. Changing of the Scanwatch’s position for recording might lead to more usable data.…”
Section: Discussionmentioning
confidence: 96%
“…To obtain a SW-ECG, patients were instructed to hold the stainless steel ring on the top case of the SW continuously for 30 s. Readings from the automated SW-algorithm (HR, PR-, and QT-interval plus QTc) were recorded and a PDF-file of the 30 s single-lead (lead I) SW-ECG was saved. QT-interval on the corresponding 12-lead ECG was manually interpreted by two blinded, independent cardiologists applying the tangent-method ( 8 ), using lead II or V5/V6 as suggested in previous work ( 6 , 8 , 9 ). Bazett’s formula was used to calculate QTc ( 10 ).…”
Section: Methodsmentioning
confidence: 99%
“… 10 Pilot data for the six-lead device have recently shown high levels of agreement with 12-lead ECGs in athletes for rhythm analysis, but not ischaemia. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, this ECG recording variant is useful for obtaining information on cardiac rhythm and electrical intervals for patients who have difficulty achieving the classic 12-lead ECG, such as the existence of mental health diseases [ 36 ]. In contrast, these methods are less reliable for determining left ventricular hypertrophy, QRS wave amplitudes, or ischemic changes [ 37 ].…”
Section: Introductionmentioning
confidence: 99%